ANALISIS KEMAMPUAN BERPIKIR ANALISIS SISWA DALAM PEMBELAJARAN IPA - Al Fatihah, Annisa; Yennita, Yennita; Fakhruddin Z, Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the level of analytical thinking skills of VII grade students of SMP Negeri 13 Pekanbaru on natural science subjects. This type of research is a survey research. The subjects of this study were 113 students who were in 3 different levels. Data collection techniques in the form of giving objective questions amounted to 27 questions with 3 aspects, where each aspect consists of 3 indicators and each indicator has 9 sub-indicators, each sub-indicator consists of 2 to 4 questions with the same or different material. Data analysis of the results of this study uses descriptive analysis, which provides an overview of students' analytical thinking skills. After doing a descriptive analysis of the research data, it was found that the average percentage of analytical thinking skills of VII grade students of SMP Negeri 13 Pekanbaru for analytical thinking skills was 41% with sufficient categories. The average percentage of students' analytical thinking skills for each aspect and each indicator is 48% with sufficient categories for distinguishing aspects, 45% with sufficient categories for organizing aspects, and 30% for aspects of compatibility with low categories.Key Words: Analytical Thinking Skills, Differentiating aspect, Organizing aspect, Atributing aspect.